REHABILITASI HUTAN MANGROVE: Pelestarian Ekosistem Pesisir Pantai dan Pemberdayaan Masyarakat Pesisir - Haryanto, Rudi (STAIN PAMEKASAN, 2012)
AbstracMadura coastal ecosystem has a variety of biological resources. It either has been productive or possesses a high quality economic value. The coastal area Aberration becomes one of the factors of the coastal ecosystem damages. Furthermore, the uncontrolled exploitation of natural resources along the coastal areas exacerbates the damage. The absence of belonging sense among the coasters toward the mangrove forest- ecosystem seems the factor either. It needs a rehabilitation of mangrove forest to anticipate as well as to discontinue the damage area. In order to apprehend this, a comprehensive maintenance of the whole stakeholders must be taken. It should involve an active participation of community in the course of community based management approach.Kata-kata Kunciabrasi, rehabilitasi, ekosistem , pesisir, mangrove, masyarakat pesisir